Injuries and risk factors in men`s beach soccer: Japanese national championships 2013-2023 - Shimakawa, T.; Galmiche, S.; Ueda, S.; Shimakawa, Y. (Science and Medicine in Football, 2025)
Understanding the most common injuries in beach soccer and their risk factors is essential for ensuring player safety. We aimed to describe the injury patterns and identify factors associated with the risk of injury in men`s beach soccer. We prospectively recorded injuries reported by players at an on-site aid station during the Japanese National Beach Soccer Championships between 2013 and 2023 (9 tournaments). Match exposure was recorded through video review. We described the injury types and sites, and the factors associated with the injury risk using generalized estimating equations in negative binomial models adjusted for confounders. In total, 796 participants played for 1360.5 player-hours. We observed 144 injuries, with an incidence rate of 106.0/1000 player-hours (95% CI: 89.9-125.0), representing 153 diagnoses. The most frequent injury sites were as follows: foot (n = 40), thigh (n = 24), and lower leg (n = 21). The most frequent injury type was contusion (n = 75). Of the 83 injuries caused by a contact with another player, 24 resulted in a foul. There were 35 injuries associated with time loss (incidence rate 25.7/1000 player-hours, 95% CI: 18.6-35.7), mainly in the foot (n=10) and the thigh (n=8). The risk of injury was lower for goalkeepers and higher in players with time-loss injuries in the past year, with trends towards higher risk for players with lower BMI and history of severe injuries. Lower limb contusions are the predominant injuries in men`s beach soccer. Our findings raise the question of protective foot gear to reduce foot contusions and fractures and can inform playing schedules of players at risk.